The Role of Lipid Rafts in Cancer Cell Adhesion and Migration - Toshiyuki Murai (International Journal of Cell Biology)
Lipid rafts are cholesterol-enriched microdomains of the cell membrane and possess a highly dynamic nature. They have been involved in various cellular functions including the regulation of cell adhesion and membrane signaling through proteins within lipid rafts. The dynamic features of the cancer cell surface may modulate the malignant phenotype of cancer, including adhesion disorders and aggressive phenotypes of migration and invasion. Recently, it was demonstrated that lipid rafts play critical roles in cancer cell adhesion and migration. This article summarizes the important roles of lipid rafts in cancer cell adhesion and migration, with a focus on the current state of knowledge. This article will improve the understanding of cancer progression and lead to the development of novel targets for cancer therapy.